The Effects of the Affordable Care Act on Labour Supply and Other Uses of Time - Anna Bottasso; Gianluca Cerruti; Maurizio Conti; Elena G. F. Stancanelli (Institute of Labor Economics (IZA), 2022)
A vast literature studies the behavioural impacts of health care reforms, often coming to controversial conclusions. Here we examine the time allocation effects of the Affordable Care Act, also known as Obama Care, focusing on two ACA pillars: Medicaid expansion, which increased access to public health insurance, and the Tax Credit Premium, subsidizing the purchase of private health insurance. Using 2012-2015 daily diary data from the American Time Use Survey, we take a triple differences-in-differences approach, which exploits the cross-state variation in the timing of ACA implementation, together with differences in income eligibility thresholds, to identify the effects at stake. Considering a sample of childless adults, a group not eligible to public health insurance before ACA, we find that the Medicaid expansion reduced their labour supply by over an hour per day, increasing part-time work, while the Premium Tax Credit raised employment by about 7 percentage points. The implications for other uses of time are also studied.
Keywords: I13; J08; J22; 330; Affordable Care Act; labor supply; time allocation